Pengalaman dan Kompetensi Profesional Guru terhadap Kinerja Guru - Taman Nilayta Ritonga (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2021)
This study aims to determine the effect of experience and professional competence on teacher performance in Madrasah Tsanawiyah Swasta, Sukajadi District, Pekanbaru. This research is field research, using a quantitative approach. research respondents amounted to 36 teachers. Data collection techniques using documentation, observation, and questionnaires. The data analysis technique used multiple linear regression formula. Based on the results of the study, it can be concluded that there is an effect of experience on teacher performance with a t value of 3.227 > t table (2.034) and a value of f (0.003 < 0.05), it can be concluded that experience has a significant effect on teacher performance. There is a professional influence on teacher performance with a t-count value of 9,024 ttable (2,034) and a f value (0.000 <0.05), it can be concluded that teacher professional competence has a significant effect on teacher performance. And there is an effect of experience and professional competence on the performance of private Madrasah Tsanawiyah teachers, Sukajadi District, Pekanbaru, obtained the value of F arithmetic > F table that is (192.063> 2.034) with a significance value of <0.05, which is 0.000. It can be concluded that the experience and professional competence of teachers have a significant effect. on teacher performance.